PENGARUH CORPORATE GOVERNANCE, FINANCIAL PERFORMANCE, DAN TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN - Hermanto, Jeanny Angel; Lekok, Widyawati (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research aims to obtain empirical evidence on whether the components of corporate governance, financial performance, and tax avoidance have an influence on firm value for non-financial companies listed in Indonesia Stock Exchange. The independent variables used in this research such as Capital Structure, Institutional Ownership, Managerial Ownership, Profitability, Tax Avoidance, Current Ratio, Firm Size, Dividend Payout Ratio, and Total Asset Turnover with the dependent variable which is Firm Value. This object of this study uses data from non-financial companies listed on the Indonesia Stock Exchange from 2020-2022 as the population. Then, the sampling process from data used purposive sampling method and used multiple regression as a method for analyzing data. This sample used in this research was 102 data from 34 companies that passed the criteria. This research states that Profitability and Tax Avoidance has positive effect on Firm Value. However, other independent variables such as the Capital Structure, Institutional Ownership, Managerial Ownership, Current Ratio, Firm Size, Dividend Payout Ratio, and Total Asset Turnover have no effect on Firm Value.